PENGARUH KECERDASAN EMOSIONAL (EQ) DANPERILAKU BELAJAR TERHADAP HASIL BELAJARPADA MATA PELAJARAN EKONOMI - Putri, Dini Handayani; Parijo,, Parijo,; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractResearch aims to understand influance between emotional quotient and  behavioral study on the student learning senior high school Muhammadiyah 1 Pontianak. The methodology this is the method descriptive to the quantitative research. Subyek the research were student social class of 80 people student. An istrument that is used is identification and documentary. In the research using analysis linear regression of multiple. Based on the result of the hypothesis a partial obtained the emotional quotient tcount 2,2272 with the probability (sig) = 0,000. Value tcount (2,2272) > ttable (1,6641) and the probability t (sig) smaller than degrees significant (0,000 < 0,05). Behavaior learn obtained the value of tcount (1,803) > ttable (1,6641) and the probability t (sig) was less than degrees significant (0,000 < 0,05). Based on the result of the hypothesis simulltaneously obtained R Square value of 0,670 or similar to 67%. Goes to show that emotional quotient and behavior learn in positive affect learning outcomes by 67% anf 33% influenced by other variables that not be researched. Keywords: Emotional quotient, Behavior study, Learning outcomes